Migration and Urbanity in Rural Areas. Developments in the German-Luxembourg Border Region. - Boesen, Elisabeth; Schnuer, Gregor; Wille, Christian (Springer VS, 2020)
Studies on the connection between migration and urbanity are usually concerned with conditions and developments in cities. The presence of 'urbanity' in rural space is the topic of the present contribution. It will be discussed using the example of residential migration in the Greater Region SaarLorLux. The massive influx of residential migrants from Luxembourg into the border regions of the neighbouring countries is a relatively recent phenomenon, the main cause of which lies in the developments in the real-estate market in the Grand Duchy of Luxembourg. This phenomenon is of special interest for the topic of migration in rural areas in two regards: because of the important demographic changes produced by the residential migrants in individual border villages and because of the complex composition of the group of residential migrants, which is extremely differentiated regarding the dimension rural—urban. Central to the article is the question, whether urban attitudes and practices become visible in German border villages, and, if so, how the migratory movement from Luxembourg influences this 'rural urbanity'. Furthermore, taking the everyday practices of the residential migrants as starting point, it asks in how far the dichotomy urbanity—rurality presents a conceptual approach for the examination of individual and structural integration processes.
Keywords: Grenzregion; Regionale Mobilität; Urbanität; Demographie; Ländlicher Raum; Wohnort; Migration